Fintech: A Conduit for sustainability and renewable energy? Evidence from R2 connectedness analysis - Polat, Onur; Ozcan, Burcu; Ertuğrul, Hasan Murat; Atılgan, Emre; Özün, Alper (Elsevier Ltd, 2024)
This study explores the evolving relationship between financial technologies (Fintech), sustainability initiatives, and the renewable energy sector. We utilize a novel R2 decomposed connectedness methodology, a significant leap from traditional analyses that mainly focus on the immediate effects, thereby missing out on the nuanced, delayed interactions that develop over time. This approach enables us to encompass both contemporaneous and lagged spillover effects, making it especially apt to examine this intricate system's dynamic interconnections. Covering the period from November 30, 2016, to November 14, 2023—marked by rapid technological advancements and an increasing global focus on sustainability—we uncover the Renewable Energy Efficiency Index's critical influence in driving fluctuations within this network. This finding is crucial amidst the current global shift towards sustainable energy practices and the vital role of technology in this transition. We note significant changes in how Fintech, sustainability, and renewable energy sectors interact over time, often in response to major global events. This observation indicates a particular vulnerability to external disturbances while presenting opportunities for strategic adaptability and creativity when confronted with these obstacles. Our research provides critical insights for readers interested in these interactions' economic and policy ramifications. For instance, the central importance of the Renewable Energy Efficiency Index emerges as a practical indicator for stakeholders aiming to steer their strategies towards more sustainable outcomes. Additionally, the variations in sector connectivity underscore the necessity for adaptable strategies amidst global uncertainties and pave the way for future investigations into the causes behind these shifts. By offering concrete recommendations, this study equips policymakers, investors, and industry leaders with the knowledge to harness the synergies between Fintech, sustainability, and renewable energy. © 2024 Elsevier Ltd
Keywords: Contemporaneous and lagged connectedness; Fintech; Renewable energy; Spillover effects; Sustainability